Draft Sixth Five Year Plan 1980-85 Vol III Sectoral Programmes Tripura - Planning Commission (Planning Commission, 1980)
According to 1971 Census, about 69% of the population of Tripura are illiterate. This percentage is much higher in case of weaker sections of, the community i.e. in the case of scheduled castes, scheduled tribes and women. Again, there is a great disparity in the literacy person age between urban and rural population.
Government of Tripura
Government of Tripura